Financial Deregulation and Consumption in the United Kingdom - Bayoumi, Tamin (The Review of Economics and Statistics, 1993)
The last decade has seen widespread deregulation of domestic financial markets in the United Kingdom. This paper uses regional data to investigate the connection between consumption and financial deregulation. It is concluded that deregulation has led to a significant increase in the forward-looking nature of aggregate consumption. Copyright 1993 by MIT Press.